Efficacy and safety of anlotinib as maintenance treatment in extensive-stage small cell lung cancer: a single-armed single center retrospective study - Jin Xiong; Lei Xia; Lei Xia; Lei Xia (Frontiers in Oncology)
IntroductionPatients with extensive-stage small cell lung cancer (ES-SCLC) have a poor Q6 prognosis and there is no standard protocol for maintenance treatment. Anlotinib as a third-line or beyond therapy for ES-SCLC was proved to be effective.MethodsWe retrospectively screened of patients with ES-SCLC who started receiving anlotinib as first-line or second-line therapy at the Second Affiliated Hospital of Chongqing Medical University from November 2018 to December 2022. 30 patients treated with anlotinib based combination therapy and subsequent maintenance therapy were included. The primary study endpoint was progression-free survival (PFS) and the secondary study endpoints were overall survival (OS), clinical response and adverse events (AEs).Results and discussionIn 30 ES-SCLC patients, the median PFS and OS were 7.2 months and 17.6 months respectively. The ORR and DCR were 50.0% (15/30) and 86.7% (26/30) respectively. The median PFS was 8.2 months and 5.6 months for patients who received synchronized immunotherapy or chemotherapy. The median OS was 20.1 months and 15.1 months for patients who received synchronized immunotherapy or chemotherapy. The median time to intracranial progression (TTP) was 7.2 months for patients who were without brain metastases before receiving anlotinib. No unexpected AEs were reported. Grade 3-4 adverse events were reported in 10 patients (33.3%). No treatment-related deaths occurred during this study. Our study has indicated the good efficacy and safety about the application of anlotinib in the maintenance therapy in the first-line or second-line treatment of ES-SCLC and it can also achieve good intracranial control.